2004
DOI: 10.1086/425359
|View full text |Cite
|
Sign up to set email alerts
|

Oral Miltefosine for Leishmaniasis in Immunocompromised Patients: Compassionate Use in 39 Patients with HIV Infection

Abstract: Oral miltefosine was administered to 39 human immunodeficiency virus (HIV)-infected patients with leishmaniasis for whom standard leishmaniasis treatment had failed. Initial response was achieved in 25 patients (64%), including 16 patients (43%) with initial parasitological cure. Repeated responses after relapse and tolerability of long courses of treatment indicate the potential for development of optimized dosage schemes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 11 publications
2
48
0
3
Order By: Relevance
“…These patients present more serious and frequent side effects than patients infected only with Leishmania (Delgado et al 1999). Their response to treatment is also poor: antimonials, amphotericin B deoxycholate and amphotericin B lipid complex are showing an effectiveness of around 60-70% (Laguna 2003), and similar figures have been reported for miltefosine (Sindermann et al 2004). …”
Section: Discussionmentioning
confidence: 77%
“…These patients present more serious and frequent side effects than patients infected only with Leishmania (Delgado et al 1999). Their response to treatment is also poor: antimonials, amphotericin B deoxycholate and amphotericin B lipid complex are showing an effectiveness of around 60-70% (Laguna 2003), and similar figures have been reported for miltefosine (Sindermann et al 2004). …”
Section: Discussionmentioning
confidence: 77%
“…Cure rates of 95% and 94% were achieved after oral administration in phase II and phase III trials in Indian patients, leading to its registration in India in 2002 (17,44). In a compassionate-use program involving 39 patients with human immunodeficiency virus-leishmaniasis coinfection, initial parasitological cure was observed in 41% of patients (41). Although miltefosine has the advantage of being an effective oral drug, its use in women of child-bearing age is restricted due to teratogenicity, which has been observed in one species (rat) with a no-effect dose level of 0.6 mg/kg.…”
mentioning
confidence: 99%
“…Mitelfosine, an alkylphosphocholine with antileishmanial activity, was used as an alternative treatment in his second episode of relapse. Studies in immunocompromised patients (human immunodeficiency virus seropositive) have shown that the antileishmanial activity of this drug is retained in this special population, suggesting that mitelfosine might be a useful option in preventing relapses of the disease [13]. Unfortunately, even after mitelfosine therapy, our patient had a new episode of VL.…”
Section: Discussion:-mentioning
confidence: 79%